Review of the Literature on Post-Pandemic Sustainable Interior Design Rating Systems from International Perspectives - Chou, Shu-Fen; Gunasagaran, Sujatavani; Zainal Abidin, Siti Norzaini; Mari, Tamil Salvi; Ibrahim, Filzani Illia (MAJ - Malaysia Architectural Journal, 2023)
Considering the prevailing pandemic, the coronavirus has successfully boosted awareness of human activities in the natural environment. This would be timely. Increasingly, customers in the COVID-19 era demand healthy, eco-friendly goods while constructing a secure and healthy interior environment for themselves. Sustainable interior design in the 21st century entails creating a good lifestyle employing green technology with little ecological consequences. Interior design companies and creatives, as well as stakeholders, are accountable for executing green design standards and education and guiding their clientele to minimise environmental pollution and inefficient use of resources even during the renovation process so that their clients may perhaps promote a decent, pleasant, and elevated living space. According to research, sustainable growth and development, economics, and the ecosystem have assumed worldwide significance. In the post-pandemic age, the creation of regionally sustainable interior design evaluation standards seems to be a pressing concern. The objectives of this paper are: (1) to approach a literature review on the global sustainable interior design rating system for directing interior design-related companies, regions, and nations to build or amend green interior design grading systems. (2) Furthermore, researchers typically aim to review the promising practices of global-level sustainable interior design grading systems as well as the green interior design indicators being developed as the essential guidelines for promoting green interior design in Taiwan as a case study in the future.